Peningkatan Kemampuan Menulis Cerpen Siswa Kelas IXA SMP Negeri 2 Babat Melalui Pemanfaatan Jurnal Pribadi - Machrus, Machrus (MADINAH, 2016)
This study aims to illustrate the improvement of the ability to write short stories through the use of personal journals at the stage of idea selection, the stage of idea development and the organizing of ideas. This study was conducted in two cycles. Each cycle is 6 x 40 minutes. The results of the implementation of the action in the form of learning process with active indicators, enthusiasm, enthusiasm, cooperation, diligent, creative and dare to increase the increase from 73.08% (cycle I) to 88.46% (cycle II). The results of the implementation of the action in the form of product results with indicators can select and summarize personal journals, develop ideas, and intrinsic clip short story, determine the journal, develop the framework of the topic, develop short stories and revise the short story showed an increase from 61.54% (cycle I) to 84, 62% (cycle II).